Імітаційне моделювання керованої осі напівпричепа - Лиходій, О. С. (НТУ "ХПІ", 2014)
В статті скомпоновані елементи керованої осі на базі існуючого напівпричепа Fliegl із подальшими рекомендаціями щодо переобладнання. Складені розрахункові схеми керованої осі та, як наслідок, її Simscape-модель.

Article arranged elements of the controlled axis based on the existing semitrailer Fliegl with subsequent recommendations for the conversion. Compound settlement schemes managed axis and, consequently, its Simscape-model that can be further used as a model of the hydraulic drive control steered axles semi-trailer to form a complex Simscape-model-train with steered axles of the semitrailer
Simulation modeling of the steering axle of the semitrailer
Keywords: керована вісь; steer-by-wire; кермова трапеція; steering axle; steering link